Green Tea Catechin-Inactivated Viral Vaccine Platform - Lee, Yun H.; Jang, Yo H.; Byun, Young H.; Cheong, Yucheol; Kim, Paul; Lee, Young J.; Lee, Yoon J.; Sung, Je M.; Son, Ahyun; Lee, Hye M.; Lee, Jinhee; Yang, Seung W.; et al. (Frontiers in Microbiology, 2017)
Traditionally, chemical agents such as formalin (FA) and β-propiolactone (BPL) have long been used for the preparation of inactivated vaccines or toxoids. It has been shown that FA extensively modifies vaccine antigens and thus affects immunogenicity profiles, sometimes compromising the protective efficacy of the vaccines or even exacerbating the disease upon infection. In this study, we show that natural catechins from green tea extracts (GT) can be used as an inactivating agent to prepare inactivated viral vaccines. GT treatment resulted in complete and irreversible inactivation of influenza virus as well as dengue virus. In contrast to FA that reacted extensively with multiple amino acids including lysine, a major anchor residue for epitope binding to MHC molecules, GT catechin epigallocatechin-3-gallate (EGCG) crosslinked primarily with cysteine residues and thus preserved the major epitopes of the influenza hemagglutinin. In a mouse model, vaccination with GT-inactivated influenza virus (GTi virus) elicited higher levels of viral neutralizing antibodies than FA-inactivated virus (FAi virus). The vaccination completely protected the mice from a lethal challenge and restricted the challenge viral replication in the lungs. Of note, the quality of antibody responses of GTi virus was superior to that with FAi virus, in terms of the magnitude of antibody titer, cross-reactivity to hetero-subtypes of influenza viruses, and the avidity to viral antigens. As the first report of using non-toxic natural compounds for the preparation of inactivated viral vaccines, the present results could be translated into a clinically relevant vaccine platform with improved efficacy, safety, productivity, and public acceptance.